COF-C4N Nanosheets with uniformly anchored single metal sites for electrocatalytic OER: From theoretical screening to target synthesis - Zhang, Rui; Liu, Wenshan; Zhang, Feng-Ming; Yang, Zhao-Di; Zhang, Guiling; Zeng, Xiao Cheng (Applied catalysis. B, Environmental, 2023)
COF-C4N, an effective oxygen evolution reaction (OER) electrocatalyst with a low overpotential, has ideal N-edge cavities for anchoring transition metal (TM) sites to achieve single atom catalysts (SACs) with higher OER activity. To screen out the optimal TM, two descriptors for characterizing the OER activities are proposed based on systematic density-functional theory calculations for two different classes of COF, TM-COF-C4N and TM-Aza-CMP. Among them, Co-COF-C4N and Ni-COF-C4N are theoretically suggested to be highly active and low-cost OER SACs for target synthesis. Followed by a series of structural characterizations (PXRD, XPS, FT-IR, EXAFS, ICP, TEM and SEM) as well as OER performance measurement, it is confirmed that Co-COF-C4N exhibits excellent OER activity with an overpotential of 280 mV at 10 mA cm−2, more active than most of previously reported OER electrocatalysts. The molecular mechanism underlying the high activity is explored. [Display omitted] •Two descriptors for characterizing OER activities were developed for SACs TM-COF-C4N.•Descriptors are generalized to other nanosheets with N-edge cavities like TM-Aza-CMP.•Co/Ni-COF-C4N are targeted synthesized as predicted low-cost efficient OER catalysts•Co-COF-C4N is verified with a very low OER overpotential of 280 mV at 10 mA cm−2.•The molecular mechanism is explored based on computed electronic properties.